Fluorescent chemigenetic actuators and indicators for use in living animals. (February 2022) - Farrants, Helen; Tebo, Alison G.
Abstract: Fluorescent indicators and actuators provide a means to optically observe and perturb dynamic events in living animals. Although chemistry and protein engineering have contributed many useful tools to observe and perturb cells, an emerging strategy is to use chemigenetics: systems in which a small molecule dye interacts with a genetically encoded protein domain. Here we review chemigenetic strategies that have been successfully employed in living animals as photosensitizers for photoablation experiments, fluorescent cell cycle indicators, and fluorescent indicators for studying dynamic biological signals. Although these strategies at times suffer from challenges, e.g. delivery of the small molecule and assembly of the chemigenetic unit in living animals, the advantages of using small molecules with high brightness, low photobleaching, no chromophore maturation time and expanded color palette, combined with the ability to genetically target them to specific cell types, make chemigenetic fluorescent actuators and indicators an attractive strategy for use in living animals. Graphical abstract: Image 1